A Case of Primary Cardiac Myeloid Sarcoma in the Absence of Lymphoproliferative and Myeloproliferative Disorders - Lisa M. Conte; Adam J. Kisling; John D. Cooper; Travis E. Harrell; Robert M. Gallagher (Annals of Internal Medicine: Clinical Cases)
Myeloid sarcoma is a rare extramedullary malignancy that is strongly associated with acute myelogenous leukemia and infrequently arises from cardiac tissue. We present a unusual case of primary isolated cardiac myeloid sarcoma identified in the absence of lymphoproliferative and myeloproliferative disorders. Tumors of unknown origin can pose a major diagnostic dilemma in patients with atypical clinical presentations. Noninvasive multimodal imaging was used to identify the mass, evaluate potential diagnoses, anticipate complications, provide surveillance, and determine potential surgical interventions. This case demonstrates the appropriate diagnostic evaluation of patients presenting with a cardiac mass and the indications for endomyocardial biopsy.